2002
DOI: 10.1097/00005768-200211000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Interval training program optimization in highly trained endurance cyclists

Abstract: The present study has shown that when HIT incorporates P(max) as the interval intensity and 60% of T(max) as the interval duration, already highly trained cyclists can significantly improve their 40-km time trial performance. Moreover, the present data confirm prior research, in that repeated supramaximal HIT can significantly improve 40-km time trial performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
187
5
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(218 citation statements)
references
References 26 publications
22
187
5
4
Order By: Relevance
“…In runners, HIT has been associated with ~3% improvements in 5-km 20 and 10-km 21 running times in middleand long-distance runners. A study investigating the effects of various HIT methods in highly trained cyclists 22 reported 40-km time-trial improvements of between 4.4% to 5.8% following 4 weeks of similar HIT protocols. For rowers, previous research has indicated that TT performance enhancement is associated with improvements in Vo 2peak values, peak power output, and power achieved at 4 mmol·L −1 lactate threshold, 23 all of which improved in response to HIT in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…In runners, HIT has been associated with ~3% improvements in 5-km 20 and 10-km 21 running times in middleand long-distance runners. A study investigating the effects of various HIT methods in highly trained cyclists 22 reported 40-km time-trial improvements of between 4.4% to 5.8% following 4 weeks of similar HIT protocols. For rowers, previous research has indicated that TT performance enhancement is associated with improvements in Vo 2peak values, peak power output, and power achieved at 4 mmol·L −1 lactate threshold, 23 all of which improved in response to HIT in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The overall small changes in this variable are likely because short-term HIT stimuli are more effective in inducing central cardiovascular adaptations (13). However, the DEC group improved by~4%.…”
Section: Performance and Physiological Adaptationsmentioning
confidence: 95%
“…The anaerobic training prescription was based on data obtained in the initial evaluation (Wingate anaerobic power test) (17), using "interval training" methods (18)(19)(20), at a frequency of three times a week, for a duration of 40 min in the first month, 50 min in the second month, and 60 min in the third month. The interval work took the form of ergometric cycle series with a load equivalent to 25 watts x 0.8% of the volunteer's weight, for 30 s, with an interval for active recovery (walking) of 3 min between series.…”
Section: Trainingmentioning
confidence: 99%